2020
DOI: 10.1016/j.annonc.2020.10.418
|View full text |Cite
|
Sign up to set email alerts
|

426P A multicenter, randomized, double-blind, phase II study of lenvatinib (LEN) in patients (pts) with radioiodine-refractory differentiated thyroid cancer (RR-DTC) to evaluate the safety and efficacy of a daily oral starting dose of 18 mg vs 24 mg

Abstract: A multicenter, randomized, double-blind, phase II study of lenvatinib (LEN) in patients (pts) with radioiodine-refractory differentiated thyroid cancer (RR-DTC) to evaluate the safety and efficacy of a daily oral starting dose of 18 mg vs 24 mg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…The data suggest that antitumor activity can continue to occur with reduced dosages of lenvatinib; however, lower starting doses could lead to inferior efficacy and not necessarily less toxicity [21]. This is supported by a recent study of lenvatinib in patients with differentiated thyroid cancer, which found that ORR was not noninferior in patients who started treatment at a lower starting dose compared with a higher dose [22]. Similar outcomes were also seen in a recent prospective study of lenvatinib plus everolimus in patients with renal cell carcinoma, in which a reduced starting dose of lenvatinib (14 mg/day) was not found to be noninferior to the approved lenvatinib starting dose of 18 mg/day [23], suggesting that optimal lenvatinib therapy may be achieved by starting at a higher dose and reducing as medically necessary following maximization of supportive care.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data suggest that antitumor activity can continue to occur with reduced dosages of lenvatinib; however, lower starting doses could lead to inferior efficacy and not necessarily less toxicity [21]. This is supported by a recent study of lenvatinib in patients with differentiated thyroid cancer, which found that ORR was not noninferior in patients who started treatment at a lower starting dose compared with a higher dose [22]. Similar outcomes were also seen in a recent prospective study of lenvatinib plus everolimus in patients with renal cell carcinoma, in which a reduced starting dose of lenvatinib (14 mg/day) was not found to be noninferior to the approved lenvatinib starting dose of 18 mg/day [23], suggesting that optimal lenvatinib therapy may be achieved by starting at a higher dose and reducing as medically necessary following maximization of supportive care.…”
Section: Discussionmentioning
confidence: 97%
“…Although the results of How et al are hypothesis‐generating as to whether a lower starting dose of lenvatinib could be considered in some patients, the retrospective nature of the analysis, which included 16 patients who received lenvatinib 20 mg/day as the starting dose, should be considered. Results from prospective cohort studies published to date (across various indications) do not support alternative lenvatinib starting doses [22, 23]. Additionally, patient‐reported health‐related quality‐of‐life data among patients with endometrial cancer from Study 309/KEYNOTE‐775 were recently presented [25] and showed that, over 12 weeks of follow‐up, similar changes in Global Health Score/quality‐of‐life outcomes were observed for patients receiving lenvatinib and pembrolizumab and those receiving treatment of physician's choice (doxorubicin or paclitaxel; −5.97; 95% CI, −8.36 to −3.58 vs. −6.98; 95% CI, −9.63 to −4.33).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates it is difficult to achieve 60% of 8w-RDI when the dose of lenvatinib is reduced to less than 14 mg/day in the early phase of the treatment. Most recently, in Study 211, a randomized phase 2 study, 18 mg/day lenvatinib starting dose did not show non-inferiority to 24 mg/day in terms of ORR [15,16]. It is reported that dose reduction and interruption is required even in patients who started lenvatinib at a reduced dose [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is no evidence showing maintained efficacy and reduced toxicity in RR-DTC patients treated with VEGFR-targeted TKI that is started at a reduced dose. A randomized phase II clinical trial which investigated if a lower starting dose of lenvatinib of 18 mg yielded comparable efficacy to 24 mg in patients with RR-DTC did not demonstrate the noninferiority of 18 mg vs. 24 mg based on the overall response rate as of week 24 (40.3% vs. 57.3%) [ 120 ].…”
Section: Other Factors For Appropriate Management Of Anti-vegfr Tkis Therapymentioning
confidence: 99%